Patients with Schizophrenia Fail to Up-Regulate Task-Positive and Down-Regulate Task-Negative Brain Networks: An fMRI Study Using an ICA Analysis Approach - Nygård, Merethe; Eichele, Tom; Løberg, Else-Marie; Jørgensen, Hugo A.; Johnsen, Erik; Kroken, Rune A.; Berle, Jan Ø.; Hugdahl, Kenneth (Frontiers in Human Neuroscience, 2012)
Recent research suggests that the cerebral correlates of cognitive deficits in schizophrenia are nested in the activity of widespread, inter-regional networks rather than being restricted to any specific brain location. One of the networks that have received focus lately is the default mode network. Parts of this network have been reported as hyper-activated in schizophrenia patients (SZ) during rest and during task performance compared to healthy controls (HC), although other parts have been found to be hypo-activated. In contrast to this network, task-positive networks have been reported as hypo-activated compared in SZ during task performance. However, the results are mixed, with e.g. the dorsolateral prefrontal cortex showing both hyper-and hypo-activation in SZ. In this study we were interested in signal increase and decrease differences between a group of SZ and HC in cortical networks, assuming that the regulatory dynamics of alternating task-positive and task-negative neuronal processes are aberrant in SZ. We compared 31 SZ to age- and gender-matched HC, and used fMRI and independent component analysis in order to identify relevant networks. We selected the independent components with the largest signal intensity increases (STG, insula, SMA, ACC and MTG) and decreases (fusiform gyri, occipital lobe, PFC, cingulate, precuneus and angular gyrus) in response to a dichotic auditory cognitive task. These independent components were then tested for group differences. Our findings showed deficient up-regulation of the executive network and a corresponding deficit in the down-regulation of the anterior default mode network during task performance in SZ when compared with HC. These findings may indicate a deficit in the dynamics of alternating task-dependent and task-independent neuronal processes in SZ. The results may cast new light on the mechanisms underlying cognitive deficits in schizophrenia, and may be of relevance for diagnostics and new treatments.